A New Method for Determining Fluid Flux at High Pressures Applied to the Dehydration of Serpentinites. (8th September 2022) - Eberhard, L.; Thielmann, M.; Eichheimer, P.; Néri, A.; Suzuki, A.; Ohl, M.; Fujita, W.; Uesugi, K.; Nakamura, M.; Golabek, G. J.; Frost, D. J.
Abstract: A new method to determine fluid flux at high pressures and temperatures has been developed and used to study serpentinites at subduction zone conditions. Drill cores of a natural antigorite‐serpentinite with a strong foliation were used in multi‐anvil experiments in the range of 2–5 GPa and 450–800°C. Fluids released upon dehydration are fixed by the formation of brucite in an adjacent fluid sink. The amount and distribution of brucite serves as a proxy for fluid flow. In our specific setup the sample reacted with the surrounding fluid sink to form an additional layer of olivine, which has the potential to limit fluid flux within our experiments. For conditions prior to serpentine dehydration we used Al(OH)3 as fluid source. Fluid in this experiment did not migrate through the serpentinite, indicating that serpentine has a low diffusivity. The experiments also show that small deviatoric stresses have an influence on the fluid flux and can cause an anisotropic fluid flux. Comparison between the time scales of the determined fluid flux with fluid production rates indicates fluid pressure buildup during dehydration reactions. Adjacent less permeable layers can inhibit fluid flux and cause fluid pressure buildup even at conditions when an interconnected pore space formed. Plain Language Summary: Subduction zones are regions where tectonic plates are recycled into the Earth's interior. Prior to subduction, the plates experienced extensive chemical interaction with the ocean water, forming hydrous minerals. Serpentine is an important hydrous mineral that can transport significant amounts of water into the Earth's interior. During subduction both pressure and temperature increase whereby hydrous minerals break down and release their water. The fluid migrates into the overlying mantle wedge, where it accounts for hydration as well as melting processes. The global flux balances would require this process to be very effective. However, it was so far not possible to measure the fluid flux at the subduction zone conditions in laboratories. In this study, we present a new method to determine the fluid flux prior and during dehydration. We found that prior to dehydration, the fluid flux in serpentinites is small. During dehydration the rocks ability to let fluids pass through increases. However, adjacent rocks with a low ability for fluid transport can further inhibit a fluid flux at these conditions. Generally, our experimental setup can be used for any system that immobilizes migrating fluids by hydration reactions. Key Points: A new method to determine fluid flux at high pressure and temperature conditions is developed Slow fluid migration in serpentinites promotes brittle fracturing in subduction zones Fast fluid migration upon dehydration of serpentinites promotes large‐scale fluid flux, if not inhibited by adjacent less permeable layers